Performance of the ATLAS Level-1 topological trigger in Run 2 - Aad, G.; Abbott, B.; Abbott, D. C.; Aliev, M.; Didenko, M; Kostyukhin, Vadim V.; Kuchinskaya, Olesya I.; Penzin, Maxim S. (The European Physical Journal C)
During LHC Run 2 (2015-2018) the ATLAS Level-1 topological trigger allowed efficient data-taking by the ATLAS experiment at luminosities up to 2.1 x10(34) cm(-2) s(-1), which exceeds the design value by a factor of two. The system was installed in 2016 and operated in 2017 and 2018. It uses Field Programmable Gate Array processors to select interesting events by placing kinematic and angular requirements on electromagnetic clusters, jets, tau-leptons, muons and the missing transverse energy. It allowed to significantly improve the background event rejection and signal event acceptance, in particular for Higgs and B-physics processes.